Foreword - Batlle, A; Rossetti, M V (Cellular and Molecular Biology, 2009)
To start with, we wish to thank Professor Dr. Raymond Wegmann "The Founding President” and Professor Dr. Jean-Michel Maixent, "The President”, Editors-in-Chief of Cellular and Molecular BiologyTM for their generous invitation to become Guest- Editor and Co-Guest Editor of this special theme issue on "Porphyrias and associated pathologies. Biochemistry and Molecular Biology”, which will be published in two Volumes, Part I, appearing now, February 16 th, 2009 and the next, Part II, scheduled for June 2009. Although Cellular and Molecular BiologyTM has already published three others special issues on this subject, one in 1997, and two in January and December 2002, ...”to have another issue on "Porphyrins and Porphyrias” is not too much, since it belongs to one of the modern problems for which orphan drugs are requested”... (quoted from Professor Dr. Raymond Wegmann, Cellular and Molecular BiologyTM, , 2002, 48, 823).